Caracterização de espécies de Candida provenientes de infecção da mucosa vulvovaginal de mulheres atendidas no Hospital das Clínicas em Goiânia-GO - Santos, Andressa Santana (2018)
Introduction:Vulvovaginal candidiasis (VVC) is characterized as the second most common infection among infections affecting this region. Candida yeasts, such as C. albicans, C. parapsilosis, C. topicalis, C. glabrata, C. krusei and C. guilliermondii, are the main causes of this pathology and can be identified by phenotypic and molecular methods. Objectives:This study determines the predictive value (PPV) of the clinical diagnosis of VVC in comparison to the culture, characterizes Candida species isolated from the vaginal mucosa through phenotypic and molecular methods, and verifies the production of hydrolytic enzymes and the susceptibility profile in vitro to antifungal agents used in VVC therapy. Methods: the phenotypic methods used were based on morphological and biochemical aspects, while molecular tests were performed using the polymerase chain reaction with primes specific for each species. In order to verify the activity of the enzymes protease, phospholipase and hemolysin, yeast growth was carried out in media containing bovine albumin, egg yolk and blood, and the reading was determined by the precipitation zone (PZ). Adherence of Candida to epithelial cells was determined by light microscopy by counting the number of cells adhered to 100 epithelial cells. In vitro susceptibility of Candida isolates to fluconazole, itraconazole, voriconazole, nystatin, and amphotericin B was performed using the broth dilution assay to determine the minimum inhibitory concentration (MIC) of the antifungal. Results: the VPP of clinical diagnosis against the gold standard of 61.8% (34/55). Among the 55 samples collected, 36 isolates identified as C. albicans(27), C. glabrata (5) and C. topicalis (4) were obtained. All isolates were enzyme producers with average adherence to 100 oral epithelial cells for the C. albicans, C. glabrata and C. tropicalis species were respectively 402.5, 236.2 and 58. High resistance to fluconazole (38.8%), high susceptibility to amphotericin B (94.4%) and low MIC values for nystatin (8 μg / mL at > 16 μg/mL) were observed for the isolates. Conclusions: the culture is essential for the diagnosis of CVV and confirm that C. albicans continues the predominant species as CVV agent. All species presented a high pathogenic power. Hydrolytic enzymes were produced by all the isolates. This study allow suggest to the clinician that the in vitro susceptibility tests prior to antifungal prescription would bring higher therapeutic success.